Evaluation of N-benzoylthiourea derivatives as possible analgesic agents by predicting their physicochemical and pharmacokinetic properties, toxicity, and analgesic activity - Suko Hardjono; Siswandono Siswandono; Rina Andayani (Universitas Gadjah Mada, 2017)
This study aimed to predict the physicochemical properties, pharmacokinetic properties (ADME), toxicity, and analgesic activity of 30 compounds of N-benzoylthiourea derivatives that are potential analgesic drugs. One of the mechanisms of action of N-benzoylthiourea derivatives is the inhibition of the cyclooxygenase-2 (COX-2) isoenzyme. An in silico test was performed by docking a compound that would predict its activity with the target COX-2 isoenzyme, PDB ID: 1PXX, using the MVD (Molegro Virtual Docker) program. The result of the docking was a form of energy bond indicated by the value of the rerank score (RS), where compounds that had lower RS values were predicted to have a higher activity. The pkCSM and Protox online tools were used to predict various physicochemical properties. Based on the RS values, the N-benzoylthiourea derivatives can be predicted to have lower analgesic activity than diclofenac, the reference ligand. Three of the N-benzoylthiourea derivatives—N-(2,4-bis-trifluoromethyl)-benzoylthiourea, N-(3,5-bis-trifluoromethyl)benzoylthiourea, and N-(3-trifluoromethoxy)-benzoylthiourea—had RS values of -90.82, -94.73, and -92.76, respectively, suggesting that these compounds were predicted to have analgesic activity relatively similar to diclofenac (RS value = -95.16). Furthermore, the majority of the N-benzoylthiourea derivatives were predicted to have good pharmacokinetic properties (ADME), and cause relatively low toxicity.